Introducing a new prognostic instrument for long-term mortality prediction in COPD patients: the CADOT index - Brat, Kristian; Svoboda, Michal; Hejduk, Karel; Plutinsky, Marek; Zatloukal, Jaromir; Volakova, Eva; Popelkova, Patrice; Novotna, Barbora; Engova, Dita; Franssen, Frits M E; Vanfleteren, Lowie E G W; Spruit, Martijn A; et al. (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2021)
OBJECTIVES: The BODE (BMI, Obstruction - FEV1, Dyspnoea - mMRC, Exercise - 6-MWT) and the ADO (Age, Dyspnoea - mMRC, Obstruction - FEV1) indices are widely used prognosis assessment tools for long-term mortality prediction in COPD patients but subject to limitations for use in daily clinical practice. The aim of this research was to construct a prognostic instrument that prevents these limitations and which would serve as a complementary prognostic tool for clinical use in these patients. METHODS AND PARTICIPANTS: The data of 699 COPD subjects were extracted from the Czech Multicentre Research Database (CMRD) of COPD patients (the derivation cohort) and analysed to identify factors associated with the long-term risk of mortality. These were entered into the ROC analysis and reclassification analysis. Those with the strongest discriminative power were used to construct the new index (CADOT). The new index was validated on 187 patients of the CIROCO+ cohort (Netherlands; the validation cohort). RESULTS: The CADOT was constructed by adding two newly identified prognosis-determining factors, chronic heart failure (CHF) and TLCO, to the ADO index. In a head-to-head comparison, the CADOT index showed highest c-statistic values compared to the BODE and ADO indices (0.701 vs 0.677 vs 0.644, respectively). The prognostic power was more definitive when applied to the Dutch validation (CIROCO+) cohort (0.842 vs 0.799 vs 0.825, respectively). CONCLUSIONS: The CADOT index has comparable prognostic power to the BODE and ADO indices. The CADOT is complementary/an alternative to the BODE (if 6-MWT is not feasible) and ADO (with less dependence on the age factor) indices. TRIAL REGISTRATION: ClinicalTrials.gov (NCT01923051).
Keywords: respirační funkční testy; prognóza; chronická obstrukční plicní nemoc; Dyspnea; Pulmonary Disease, Chronic Obstructive; COPD; Prognosis; index tělesné hmotnosti; prognostic index; stupeň závažnosti nemoci; lidé; dyspnoe; pulmonary function; Humans; mortality; Body Mass Index; Respiratory Function Tests; Severity of Illness Index